Teacher interpersonal behaviour: Its influence on student motivation, self-efficacy and attitude towards science - Reid, Catherine (Curtin University, 2007)
The effect that teacher interpersonal behaviour has on motivating students to want tolearn and on nurturing student self-efficacy in the science classroom cannot beunderestimated. Teacher interpersonal behaviour can be perceived to be the catalystthat determines the level of student self-efficacy in classroom activities. An analysisof effective classroom teaching has been assessed in recent times in relation toteacher interpersonal behaviour. However, the effect that teacher interpersonalbehaviour has on student motivation has not been studied.The aim of this study was to identify the interpersonal skills of teachers that areperceived to encourage a motivating classroom environment. It also describedstudents' perceptions of teacher interpersonal behaviour and classroom environment,and assessed the significant impact teacher interpersonal behaviour had on studentself-efficacy and student attitude towards science. Student data were collected from313 year 8, 9 and 10 science students in 12 classrooms in a girls' secondary school inBrisbane, Australia. They were studying a general science course that coveredaspects of biology, chemistry and physics. Qualitative and quantitative data werecollected. The study confirmed the validity and reliability of the Questionnaire onTeacher Interaction (QTI) and the Students' Motivation, Attitude and Self-Efficacy inScience (SMASES) questionnaire. Thus, the study identified perceptions of teacherinterpersonal behaviour and classroom environment, and investigated associationsbetween the results obtained from the analysis and the other instruments that wereadministered in the study. The study identified that there was a significantrelationship between teacher interpersonal behaviour and its effect on studentmotivation, self-efficacy and attitude towards science.